Administrative decentralization in Iraq’s constitution 2005 - سعيد اقبال ناجي (Journal of Legal Sciences, 2020)
After the occupation of Iraq and the overthrow of its regime on 9 April 2003, thinking was going to reshape the shape of the Iraqi State from a unified state to a federal state. In 2004, the Iraqi Governing Council passed the Transitional Administration Law, article 4 of which states that "the Iraqi regime is a federal, democratic and pluralistic republic." In Iraq’s permanent federal constitution in 2005, he explained in his first article: "The Republic of Iraq is an independent and sovereign state, with a federal parliamentary parliamentary system of government Some problem added to the problems of Iraq and its crises. The research is based on two assumptions that Iraq needs a decentralized system, both political and administrative, to deal with the problems of Iraq, especially the problem of rights, and to consolidate democracy, establish it and build the state. The crises in Iraq will not end immediately if administrative decentralization and federalism are applied, but they will be mastered and controlled, and will be properly resolved rather than chaotic and conflictful for conflict